2021
DOI: 10.3390/diagnostics11101794
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Predictors of Progression Interstitial Lung Disease in Rheumatoid Arthritis Compared with Other Autoimmune Disease: A Retrospective Cohort Study

Abstract: Objectives: To describe the characteristics and progression of interstitial lung disease in patients with associated systemic autoimmune disease (ILD-SAI) and to identify factors associated with progression and mortality. Patients and methods: We performed a multicenter, retrospective, observational study of patients with ILD-SAI followed between 2015 and 2020. We collected clinical data and performed pulmonary function testing and high-resolution computed tomography at diagnosis and at the final visit. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…Another study of IPF patients showed that current or former smokers had longer survival than never smokers [47]. In patients with autoimmune disease associated ILD, current or former smoking was associated with disease progression and mortality [48] whereas, in a study of patients with RA-ILD, the survival was similar between current or former and never smokers [49]. In our study, never smoking was associated with the risk of disease progression in ILD and never smokers had shorter median survival than current or former smokers.…”
Section: Table 1 Characteristics Of Patients With Progressive Ild And...mentioning
confidence: 99%
“…Another study of IPF patients showed that current or former smokers had longer survival than never smokers [47]. In patients with autoimmune disease associated ILD, current or former smoking was associated with disease progression and mortality [48] whereas, in a study of patients with RA-ILD, the survival was similar between current or former and never smokers [49]. In our study, never smoking was associated with the risk of disease progression in ILD and never smokers had shorter median survival than current or former smokers.…”
Section: Table 1 Characteristics Of Patients With Progressive Ild And...mentioning
confidence: 99%
“…The multivariate analysis also showed that, in patients with RA-ILD treated with abatacept, the more pronounced impairment of FVC and DLCO at initiation of treatment was associated with poorer progression of lung disease. This finding has been reflected in various studies, thus pointing to an association with greater progression of lung disease and mortality [53,54]. However, less attention has been given to the analysis of factors associated with progression and mortality in patients with RA-ILD treated with abatacept.…”
Section: Discussionmentioning
confidence: 98%
“…The FVC of all patients (n=204) was 72±16.6 (mean ± SD) and at the end of the study was 68.2±16.2(mean ± SD). [29] Multiple studies showed the correlation between the PFT and CT lung scoring system using different modalities.…”
Section: Discussionmentioning
confidence: 99%